158k views
4 votes
Simply the equation x+1/y-1=1

User MinchinWeb
by
5.0k points

2 Answers

5 votes

Answer:

y = x + 2, where y can not be 0

Explanation:

(x+1)/(y-1) = 1

x+1 = y-1

y = x+1+1

y = x + 2, where y can not be 0

Because whey y = 0, the denominator becomes 0 and the function becomes undefined

User SirDerpington
by
5.6k points
6 votes

Answer:

= x - y + 2

Explanation:

x+1/y-1=1

First step, multiply both sides by y - 1 or cross multiply

((x + 1) × (y - 1))/ y - 1 = 1 × (y - 1)

x + 1 = y - 1

x - y + 1 + 1 =0

= x - y + 2

User Selwyn
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.